MONEY WAQF REGULATION AND DYNAMICS OF PRODUCTIVE WAQF ASSET GOVERNANCE: A SOCIO LEGAL STUDY ON THE QURANI PAMEKASAN INSAN FOUNDATION - Samheri; Misbah Zulfa Elizabeth; Ahmad Furqon; Achmad Gunaryo (Academic Bright Collaboration, 2026)
This study aims to examine the renewal of cash waqf regulations in Indonesia, analyze their implementation in the management and development of waqf assets at the Insan Qur’ani Indonesia Foundation in Pamekasan, and identify the socio-economic impacts of such implementation. This research employs a qualitative field research approach with a socio-legal perspective. Data were collected through in-depth interviews, observations, and document analysis involving key informants within the foundation. The findings indicate that the renewal of waqf regulations, particularly after the MUI Fatwa (2002), Law No. 41 of 2004, and Government Regulation No. 42 of 2006, has significantly transformed the paradigm of waqf management in Indonesia. The implementation of cash waqf at the Insan Qur’ani Foundation has enhanced community awareness, supported the development of productive waqf in sectors such as agriculture, trade, and livestock, and contributed to expanding access to education and employment opportunities. This study is limited to a qualitative case study approach within a single institution; therefore, future research is recommended to conduct broader empirical studies across different regions and institutions to validate these findings. This study provides a socio-legal analysis of the practical implementation of cash waqf in a pesantren-based institution, offering empirical insights into productive waqf governance at the local level in Indonesia.